The influence of digital leadership on innovative performance through work engagement in Generation Z employees in Bali - I Gede Ary Ardika; Nyoman Sri Subawa; Caren Angellina Mimaki (Journal of Economics and Business Letters, 2026)
This study investigates the impact of digital leadership on innovative performance through the mediating role of work engagement among Generation Z employees in Bali. This study adopts a quantitative approach using a survey design, with data collected from 100 respondents selected through purposive sampling. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used for the analysis. The findings reveal that work engagement positively and significantly impacts innovative performance, while digital leadership boosts work engagement in a statistically meaningful way; however, it fails to directly influence innovative performance to a significant degree. Moreover, the full mediation by work engagement in the link between digital leadership and innovative performance suggests that employee engagement channels the innovation-boosting effects of digital leadership. These findings imply that digital leadership indirectly improves innovative performance by first enhancing employees’ work engagement. Therefore, organizations are encouraged to strengthen digital leadership practices while simultaneously fostering higher levels of engagement among employees, particularly Generation Z workers, to support innovation in a digitally oriented work environment.